Engineering Carbon Nanotube Forest Superstructure for Robust Thermal Desalination Membranes. (19th June 2019) - Sun, Meng; Boo, Chanhee; Shi, Wenbo; Rolf, Julianne; Shaulsky, Evyatar; Cheng, Wei; Plata, Desiree L.; Qu, Jiuhui; Elimelech, Menachem
Abstract: Desalination by membrane distillation (MD) using low‐grade or waste heat provides a potential route for sustainable water supply. Nonwetting, porous membranes that provide a selective pathway for water vapor over nonvolatile salt are at the core of MD desalination. Conventional water‐repelling MD membranes (i.e., hydrophobic and superhydrophobic membranes) fail to ensure long‐term desalination performance due to pore wetting and surface fouling. To address these challenges, a defect‐free carbon nanotube forest (CNTF) is engineered in situ on a porous electrospun silica fiber substrate. The engineered CNTF forms an ultrarough and porous interface structure, allowing outstanding wetting resistance against water in air and oil underwater. As a result of this antiwetting property, the composite CNTF membrane displays a stable water vapor flux and a near complete salt rejection (>99.9%) in the desalination of highly saline water containing low surface tension contaminants. The antimicrobial property of the composite CNTF membrane imparted by the unique forest‐like architecture and the oxidative effect of carbon nanotubes (CNTs) are further demonstrated. The results exemplify an effective strategy for engineering CNT architecture to elucidate the structure–property–performance relationship of the nanocomposite membranes and to guide the design of robust thermal desalination membranes. Abstract : A novel thermal desalination membrane is developed via in situ engineering of a carbon nanotube forest (CNTF) superstructure on a porous nanofiber. Precise design of the CNTF architecture results in an ultrarough and porous interface structure, endowing the composite membrane with outstanding wetting resistance against both water and oil, stable water vapor flux, and a near complete salt rejection (>99.9%).